2013
DOI: 10.1002/ange.201207962
|View full text |Cite
|
Sign up to set email alerts
|

Potassium–Alkane Interactions within a Rigid Hydrophobic Pocket

Abstract: Kaliumkomplexe eines extrem starren und sperrigen NON‐Donorliganden wurden hergestellt. Die Festkörperstrukturen (siehe Bild) zeigen bemerkenswert kleine Kalium‐Alkan‐Abstände, und DFT‐Rechnungen belegen eine elektrostatische kationeninduzierte Kalium‐Alkan‐Wechselwirkung, die durch Wechselwirkungen zwischen dem Alkan und dem umgebenden Ligandengerüst unterstützt wird.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…Neither of these complexes is stable on solvation. Related structural diffraction studies come from the binding of light alkanes to iron centers in an extended metal–organic framework as characterized by powder neutron diffraction experiments, e.g., F . , Complexes in which there is a close intermolecular approach of an alkane to a group 1 cation (K + ) have also been reported, although these interactions are characterized as being weakly electrostatic and are further stabilized by interactions between the alkane and a hydrophobic ligand pocket …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither of these complexes is stable on solvation. Related structural diffraction studies come from the binding of light alkanes to iron centers in an extended metal–organic framework as characterized by powder neutron diffraction experiments, e.g., F . , Complexes in which there is a close intermolecular approach of an alkane to a group 1 cation (K + ) have also been reported, although these interactions are characterized as being weakly electrostatic and are further stabilized by interactions between the alkane and a hydrophobic ligand pocket …”
Section: Introductionmentioning
confidence: 99%
“…Related structural diffraction studies come from the binding of light alkanes to iron centers in an extended metal−organic framework as characterized by powder neutron diffraction experiments, e.g., F. 32,33 Complexes in which there is a close intermolecular approach of an alkane to a group 1 cation (K + ) have also been reported, although these interactions are characterized as being weakly electrostatic and are further stabilized by interactions between the alkane and a hydrophobic ligand pocket. 54 Recognizing that a significant barrier to characterizing σalkane complexes in the solid state by X-ray diffraction is their instability in solution on the time scales and at the temperatures required for the production of single crystals, we recently reported the use of solventless conditions, 55 i.e., gas/solid reactivity, to synthesize a σ-alkane complex directly in the solid state, Scheme 1. In this crystal-to-crystal transformation, 56−62 a crystalline norbornadiene (NBD) Rh precursor, [1-NBD]-[BAr F 4 ], was treated with dihydrogen, resulting in addition of H 2 to the diene to form directly a saturated norbornane (NBA) fragment bound to the Rh(I) center through two 3c-2e Rh…”
Section: Introductionmentioning
confidence: 99%
“…Despite the accepted role of σ-alkane complexes as intermediates in these processes, ,, σ-alkane complexes are difficult to observe, as, due to a combination of strong nonpolar C–H bonds and steric interactions from alkyl groups, alkanes are poor ligands, coordinating only weakly to metal centers. , Their direct observation generally relies upon generation in solution and detection in situ using low-temperature NMR spectroscopy and time-resolved infrared spectroscopy (TR-IR); either by photogeneration of the alkane complex by loss of, for example, a CO ligand or direct protonation of an Rh–alkyl bond. Such observations build upon earlier matrix isolation experiments . Initially serendipitous single-crystal X-ray diffraction studies have shown alkane C–H bonds in close approach with metal centers (Fe 2+ , U 3+ , K + ), in which host–guest interactions with alkane ligands are suggested to play an important role. Examples where a σ-alkane complex is observed which then undergoes C–H activation are even less common.…”
Section: Introductionmentioning
confidence: 99%
“…Eine ungewöhnlich starke Koordination tritt zwischen den Kaliumionen und Alkanen in der hydrophoben Koordinationsstelle von 2,6‐Dimesitylanilin‐basierten Xanthenbisamiden (2 ) auf. Dabei ist das Kaliumion an die beiden Mesitylgruppen über π‐Wechselwirkungen koordiniert und geht darüber hinaus eine Wechselwirkung mit den CH3‐Gruppen von zusätzlich koordinierten Alkanen ein 9…”
Section: Alkali‐ Und Erdalkalimetalleunclassified